Tujuan Pendidikan Islam Dalam Al-Qur’an : Kajian Surat Az-Zariat Ayat 56 - Luthfiana Nurlathifah; Mia Lisartika (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
Jinn and humans were created to worship, but Allah SWT granted jinn and humans freedom of choice regarding worship with the consequences of that choice being accounted for in the afterlife. This research aims to discuss the meaning of jinn and humans, explain the basic meaning of the word al-ins, describe jinns and humans conceptually in the Qur'an, explain the relationship between these two creatures in the context of worship in the QS. Adz-Dzariyat 56 as an educational goal in the Al-Qur'an: study of the letter Ad-Dzariat verse 56. The research method used is qualitative through literature study. This research examines the interpretation of Surah Adz-Dzariyat verse 56 regarding the meaning of jinn, al-ins, the nature of worship and its relevance to educational purposes from various interpretive points of view and is strengthened by other verses of the Qur'an. al-ins in the Koran which has the burden of mukallaf.